PENGARUH THIN CAPITALIZATION DAN PROFITABILITAS TERHADAP PENGHINDARAN PAJAK PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Agung Setiawan; Neo Agustina (LPPM STIE Lhokseumawe, 2018)
This study was conducted at a manufacturing company listed on the Indonesia Stock Exchange and aims to see the influence of Thin Capitalizatian and Profitability on Tax Evasion in Manufacturing Companies listed in Indonesia Stock Exchange. The data used in the study are secondary data sourced from Indonesia Stock Exchange. Data analysis method used in this research is multiple linear regression with the help of program package SPSS 18.00 For Windows. The results of this study indicate that Thin Capitalization variables positively influence against Tax evasion, while Profitability variables negatively affect Tax evasion, but together Thin Capitalization and Profitability variables positively affect the Avoidance of Tax on Manufacturing Companies listed on the Indonesia Stock Exchange